Hybrid Digital-Manual Elementary Student Transfer Services: Good Governance Analysis at North Jakarta Education Sub-Department II - Hirzan Mahdafikia; Muhammad Ridhwan (Jurnal Studi Ilmu Sosial dan Politik, 2026)
Purpose: This study examines how partial digitalization shapes good governance in elementary school student transfer services at the Education Sub Department of Region II, North Jakarta, within a digital–manual hybrid model. Methodology: This study employed a descriptive qualitative approach. Data were collected through in-depth interviews with education officials and parents, supported by observation and document analysis. Informants were selected using snowball sampling, and data credibility was ensured through the triangulation of sources and methods. Results: SPBE implementation through the Dapodik system improved data organization and accessibility, but student transfer services still operate under a digital–manual hybrid model. This structure creates inefficiencies, such as long processing times, duplicated work, fragmented accountability, limited traceability, and uneven transparency of information. Conclusions: This study shows that partial digitalization alone does not ensure effective governance. The persistence of manual procedures within digital systems weakens efficiency, transparency, and accountability, indicating that governance quality depends on the level of integration between technology and organizational processes. Limitations: This study is limited to elementary school transfer services in a single regional education office and relies on the qualitative perceptions of key informants. Contributions: Beyond its context, this study contributes to public administration theory by framing student transfer services as digital manual hybrid governance and demonstrating how incomplete digital integration limits good governance while informing SPBE-based service reform in education.